2023
DOI: 10.1038/s41598-023-38684-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired ATF3 signaling involves SNAP25 in SOD1 mutant ALS patients

Abstract: Epigenetic remodeling is emerging as a critical process for several neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Genetics alone fails to explain the etiology of ALS, the investigation of the epigenome might therefore provide novel insights into the molecular mechanisms of the disease. In this study, we interrogated the epigenetic landscape in peripheral blood mononuclear cells (PBMCs) of familial ALS (fALS) patients with either chromosome 9 open reading frame 72 (C9orf72) or super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Altered expression of MAP1B [557], EGFR (epidermal growth factor receptor) [554], SREBF1 [769] and CREB1 [770] promotes Parkinson’s disease. MAP1B [637], EGFR (epidermal growth factor receptor) [636], NEDD4L [632], hsa-mir-21-5p [771], ATF3 [772] and SREBF1 [773] were significantly altered in patients with amyotrophic lateral sclerosis. A previous study reported that the EGFR (epidermal growth factor receptor) [658], hsa-mir-21-5p [762] and SREBF1 [774] biomarkers were associated with the dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of MAP1B [557], EGFR (epidermal growth factor receptor) [554], SREBF1 [769] and CREB1 [770] promotes Parkinson’s disease. MAP1B [637], EGFR (epidermal growth factor receptor) [636], NEDD4L [632], hsa-mir-21-5p [771], ATF3 [772] and SREBF1 [773] were significantly altered in patients with amyotrophic lateral sclerosis. A previous study reported that the EGFR (epidermal growth factor receptor) [658], hsa-mir-21-5p [762] and SREBF1 [774] biomarkers were associated with the dementia.…”
Section: Discussionmentioning
confidence: 99%
“…PNPLA3 [174], ACTN2 [175], MMP15 [176], SVEP1 [177], CPB2 [178], DYSF (dysferlin) [179], ADAMTSL2 [180], NINJ2 [181], LRP2 [106], PHLDA3 [182], LIPC (lipase C, hepatic type) [183], CARNS1 [184], PRODH (proline dehydrogenase 1) [185], TRPV6 [186], CNDP1 [187], DHCR7 [188], KCNE5 [189] SAA1 [190], ADSS1 [191], ACADS (acyl-CoA dehydrogenase short chain) [192], ADAP1 [193], KLK10 [194], HCN2 [195], F11 [196], RNASE1 [197], GNLY (granulysin) [198], EVA1A [199], CIRBP (cold inducible RNA binding protein) [200], EDIL3 [201], NOXA1 [202], ANGPTL2 [203], CYP2A6 [204] and CTNNA3 [205] might be associated with cardiovascular diseases progression. The abnormal expression of CCL18 [206], EOMES (eomesodermin) [207], GZMA (granzyme A) [208], HLA-DRB5 [209], GPNMB (glycoprotein nmb) [210], PRPH (peripherin) [211], HGF (hepatocyte growth factor) [212], TTR (transthyretin) [213], VEGFA (vascular endothelial growth factor A) [214], CHI3L1 [215], AATK (apoptosis associated tyrosine kinase) [216], SREBF1 [217], OLIG2 [218], ATF3 [219], NGFR (nerve growth factor receptor) [220], ADAMTS4 [221], LMNA (lamin A/C) [222], MT3 [223], DAO (D-amino acid oxidase) [224], AATK (apoptosis associated tyrosine kinase) [216] and LGALS3BP [225] might be related to the progression of amyotrophic lateral sclerosis. SLAMF7 [226], GPR174 [227], FCRL3 [228], SLAMF6 [229], EOMES (eomesodermin) [230], CCR4 [231], CCR2 [232], CD48 [233], CD3E [234], CCL26 [235], CCL4 [236], SLAMF1 [237], CD24 [238], IKZF3 [239], CD2 […”
Section: Discussionmentioning
confidence: 99%